The role of family functioning in marital commitment: the moderating effect of adult attachment style - Marwaziah, Ratu Syafira; Tarmidi; Fauziah, Rahma (JOURNAL OF Mental Health Concerns, 2025)
Background: The number of divorces reached 29% of the number of marriages that occurred in 2023, a notable increase compared to 2010, which only reached 4-6%. Various reasons that can cause separation make it very important to have marital commitment. Purpose: To explored the role of family functioning in marital commitment with adult attachment style as a moderator in early adults. Method: A quantitative study with 208 respondents aged between 20 and 39 years, 48 married men and 160 married women. The Indonesian adapted version of the Investment Model Scale, General Functioning of the McMaster Family Assessment Device, and Attachment Style Questionnaire were used as instruments. Results: The results of this study found that family functioning has a role in contributing to marital commitment by 47%, and moderated regression analysis showed that only dismissing attachment style moderated the role of family functioning on marital commitment. Conclusion: This finding is likely because factors such as the presence of children, religious values, social stigma, and positive views on marriage problems play a more important role in influencing marital commitment than adult attachment style. Keywords: Adult Attachment Style; Early Adulthood; Family Functioning; Marital Commitment.